TANTANGAN PELAKSANAAN LIBERALISASI MEREK DALAM PERDAGANGAN BEBAS DI KAWASAN ASEAN - Delfiyanti, Delfiyanti (UNES Journal of Swara Justisia, 2023)
The ASEAN states have put an interest toward the intellectual right, including brand by trading liberalization regionally through the ASEAN Economic Community. In accordance with the recently progressive development in good and service trading, it is not surprising when the brand play a significant rule to be recognized as the mark of particular product in common and have a power and benefit when it has been managed appropriately. In recent free trading era, brand is not just the word only connected to the product or goods, but the process and business strategy also. Therefore, it has the value or equity. By the reason, the problem of research has depicted; first, how the juridical review of law amendment of brand and geographic indication on trading liberalization; and secondly, how the implication toward the regulation of brand right and geographic indication in Indonesia. The method used in research is literature study on normative law and it is the descriptive study with analysis and qualitative. Indonesia has completes the previous act of brand and publishing a new one, Act No. 20 of 2016 on Trademark and Geographic Indication. It has given many new regulations on brand such as including nonconventional brand involves 3D brand, voice, and hologram into the regulation and also provide the specific regulation in correlation with geographic indication. It is arranged in correlation with adjustment of stipulation in international society, ASEAN especially. For Indonesia, it has become a challenge and opportunity to implement the new Act of Brand, and use the agreement in properly all at once, as well as harmonizing the new brand regulation to the existing one in ASEAN. Therefore, it is required the legal protection of intellectual right in order to the trading liberalization in ASEAN Economic Community and the implication to Indonesia.